The financial burden of out‐of‐pocket healthcare expenses on caregivers of children with atopic dermatitis in the United States - Raj Chovatiya; Wendy Smith Begolka; Isabelle J. Thibau; Jonathan I. Silverberg (Wiley, 2023)
Abstract Background Atopic dermatitis (AD) is associated with elevated financial costs, including out‐of‐pocket (OOP) expenses. Yet, the full burden of OOP expenses in children with AD is poorly understood. Objectives We sought to characterise categories, impact, and associations of caregiver‐reported OOP AD healthcare expenses for US children. Methods An online survey was administered to National Eczema Association members (N = 113 502). Inclusion criteria (US resident; respondent age ≥18; self or caregiver report of AD diagnosis) was met by 77.3% (1118/1447) of those who completed the questionnaire. Results Caregivers of children (<18 years) with AD reported increased healthcare provider (HCP) visits, comorbid food allergy, cutaneous infections, and topical antimicrobial use (p < 0.005 for all), and increased OOP expenses for hospitalisation, emergency room visits, emollients, hygiene/bathing products, childcare, and specialised cleaning products, and clothing/bedding (p < 0.05 for all) compared to adults with AD. Children with AD had increased median total yearly OOP expenditures ($860 vs. $500, p = 0.002) and were more likely to spend ≥$1000 OOP per year (48.9% vs. 40.0%, p = 0.03). In children, yearly OOP expenses ≥$1000 were associated with increased AD severity, flares, HCP visits, prescription polypharmacy, and step‐up therapy use (p < 0.005 for all) compared with adults. Predictors of harmful financial impact among children included black race (adjusted OR [95% confidence interval]: 3.86 [1.66-8.98] p = 0.002) and ≥$1000 annual OOP expenditures (6.98 [3.46-14.08], p < 0.0001). Conclusion Children with AD have unique and increased OOP expenses that are associated with significant disease burden. Strategies are needed to reduce OOP costs and improve clinical outcomes in children with AD.